Significant enhancement of critical current density in H+-intercalated FeSe single crystal. (1st July 2022) - Meng, Yan; Wei, Wei; Xing, Xiangzhuo; Yi, Xiaolei; Zhou, Nan; Zhang, Yufeng; Liu, Wenhui; Sun, Yue; Shi, Zhixiang
Abstract: Superconducting transition temperature ( T c ) and critical current density ( J c ) are two key factors that are not only crucial for probing high temperature superconducting mechanism, but also for practical applications. The simple crystal structure of FeSe is very favorable for the fabrication of thin films and wires, but its application is limited by the relatively low T c and small J c . Previous studies have found that the T c of FeSe can be significantly enhanced over 40 K by using protonation method. Here, we present a systematic study of J c and vortex properties of H + -intercalated FeSe (H x -FeSe) single crystals. The value of J c for H x -FeSe single crystal is significantly enhanced, exceeding 1.3 × 10 6 A cm −2 at 4 K, which is more than two orders of magnitude larger than 1.1 × 10 4 A cm −2 of pristine FeSe. The vortex pinning mechanism of H x -FeSe is found to be surface pinning, which is different from the dominant strong point-like pinning in pristine FeSe. Moreover, the systematic study of the vortex phase transition and the underlying mechanism provides a wealth of information for the vortex phase diagram of H x -FeSe single crystal. Our results confirm that the introduction of H + intercalations into FeSe not only enhance the T c but also significantly increases the value of J c, which is favorable for practical applications.